Sustainable supply chain in food industries: Drivers and strategic sustainability orientation - Korosh Emamisaleh; Kamaleddin Rahmani (Cogent Business & Management, 2017)
Today, the concept of sustainable development in supply chain management is introduced as one of the basic concepts in production management. Paying attention to economic, social and environmental needs of the society is essential in gaining competitive advantage in the global market. Therefore, in order to achieve sustainable development, appropriate programs and strategies should be considered by managers throughout the supply chain. Moreover, the internal and external drivers of the environment in the supply chain will lead organizations—willingly or not—towards sustainability. Hence, this paper examines the internal and external drivers in order to study strategic sustainability orientation. The results showed that internal drivers, including attitudes of managers and their support for sustainable programs, has a positive impact on strategic sustainability orientation. The study showed that external drivers of the organizations affect internal drivers, and compared to external drivers, internal drivers have a more important role in creating sustainable orientation within an organization. In addition, the mediating role of internal drivers in relation to external drivers and strategic sustainability orientation is approved. This study is conducted on 120 food industry companies of Iran.
Keywords: 650